Transformational school leadership in Indonesia: A qualitative analysis - A'yun, Ummu Qurrota; Sulisworo, Dwi; Maryani, Ika (International Journal of Education and Learning, 2024)
This study aims to explore the practices and impact of transformational school leadership within the context of Indonesian education. Using a qualitative research design, the study employed semi-structured interviews with school principals, administrative staff, and teachers to gather in-depth insights into leadership behaviors, challenges, and outcomes. The data were analyzed using NVivo 12 software, following thematic coding techniques to identify recurring themes and relationships. The findings reveal that transformational leadership positively influences educational outcomes, school climate, and organizational effectiveness. Leaders who demonstrated clear vision, empathy, and the ability to motivate others contributed to enhanced student achievement, innovative teaching practices, and improved institutional performance. Despite these benefits, school leaders also face significant challenges, including limited resources, internal resistance, and external stakeholder constraints. However, these challenges can be navigated through strategies such as inclusive leadership, collaborative problem-solving, and investment in professional development. This study concludes that transformational leadership holds considerable promise for driving educational improvement and development in Indonesia. It underscores the importance of leadership training and policy support to cultivate leaders who can inspire change, adapt to contextual complexities, and build resilient school communities.